KARAKTERISTIK BANK TARGET AKUISISI ASING (CROSS-BORDER) DAN DOMESTIK PADA PERBANKAN INDONESIA - Yutrizal Jacoub; Dedi Budiman Hakim; Sri Hartoyo; Perdana Wahyu Santosa (Universitas Mercu Buana, 2020)
The aims of this paper were to study the difference in the characteristic of acquisition target bank for cross-border and domestic over the period of 2002 – 2017 in Indonesia banking industry. There were 41 transactions of merger and acquisition during the period, and hence there was 31 ownership of private local banks have been transferred to foreign/cross-border investor. The data was obtained from Otoritas Jasa Keuangan (OJK) consists of financial publication reports of 24 banks sample and also annual reports of those banks. The methods used were descriptive statistics and independent sample test for both parametric and non-parametric data. The results show that: i) There is a significant difference on the profitability (ROE), asset size, cost efficiency, quality of loans, and liquidity between both groups of the target banks; ii) Whereas ROA and capitalization (CAR) are not different for both group of the target banks; iii) Target banks for cross border acquisition is public bank which is different with non-public banks for domestic acquisition.